A flexibilização de direitos por meio da negociação coletiva - Falleiros, Luiz Gustavo Mendes de Paula (2022)
The purpose of this work is to study labor relations, in particular, regarding the possibility of making labor rights more flexible through a collective norm under the constitucional perspective, observing the principles of human dignity, protection and the most favorable norm. The evolution of labor law, both individual and collective labor law, is approached, going through analyses of different periods until its consolidation in post-modernity, allied, still, with the philosophical perspectives that are perfectly applicable the constant evolutions in the individual and collective relations of work. Mainlu, a study is necessary to elucidate the creation, evolution and structuring of this autonomous branch of law as an object, in first, as a source of increase in the social condition of the worker and the form that, currently has been misrepresented for use in order to relativize labor relations, making it possible to make rights more flexible through collective norms. In the aspect, we cite the strong neoliberal current that was able to deconstruct a historical paradigm of labor relations, worker protection, and bring the indscriminate use the institute of the prevalence of the negotiated over the legislated as a way of flexibilizing worker’s rights. Finally, the constitucional perspective of the new interpretation on the flexibilization of labor standards is evaluated, in particular the prevalence of negotiated over the legislated, in relation to the principles of human dignity and the principle of worker protection, within the dynamics of maximum effectiveness of fundamental rights and what role the judiciary could play